2011
DOI: 10.3109/01480545.2010.520017
|View full text |Cite
|
Sign up to set email alerts
|

Vernolide-A, a sesquiterpene lactone fromVernonia cinerea,induces apoptosis in B16F-10 melanoma cells by modulating p53 and caspase-3 gene expressions and regulating NF-κB-mediated bcl-2 activation

Abstract: In this study, we investigated the effect of vernolide-A on the induction of apoptosis as well as its regulatory effect on the activation of transcription factors in B16F-10 melanoma cells. Treatment of B16F-10 cells with nontoxic concentrations of vernolide-A showed the presence of apoptotic bodies and induced DNA fragmentation in a dose-dependent manner. Cell-cycle analysis and TUNEL assays also confirmed the observation. The proapoptotic genes, p53, Bax, caspase-9, and caspase-3, were upregulated in vernoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Upon activation, IκB becomes phosphorylated, a process that targets it for ubiquitination and degradation by proteasomes. This activation results the rapid translocation of NF-κB to the nucleus, where it binds to κB binding sites in the promoter region of target genes, and induces the transcription of pro-inflammatory mediators, including iNOS, COX-2, TNF-α, IL-6 and others (Perkins, 1997; Pratheeshkumar and Kuttan, 2011c; Wang et al , 2012). Previous studies have shown that NF-κB activation occurs in responses to several environmental carcinogens (Ding et al , 2006; Ouyang et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon activation, IκB becomes phosphorylated, a process that targets it for ubiquitination and degradation by proteasomes. This activation results the rapid translocation of NF-κB to the nucleus, where it binds to κB binding sites in the promoter region of target genes, and induces the transcription of pro-inflammatory mediators, including iNOS, COX-2, TNF-α, IL-6 and others (Perkins, 1997; Pratheeshkumar and Kuttan, 2011c; Wang et al , 2012). Previous studies have shown that NF-κB activation occurs in responses to several environmental carcinogens (Ding et al , 2006; Ouyang et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Active mitochondrial dehydrogenases in living cells metabolize MTT to a purple formazan dye, which is measured photometrically at 570 nm using a spectrophotometer as described previously (Pratheeshkumar and Kuttan, 2011c). …”
Section: Methodsmentioning
confidence: 99%
“…Recently, many sesquiterpene lactone compounds have been shown to induce apoptosis in various cancer cell lines through inhibition of NF-jB activation (31)(32)(33). Inhibition of TNFainduced NF-jB activation results in apoptosis by recruiting caspase 8, indicating that TNFa can induce either prosurvival or apoptotic pathway (34).…”
Section: Discussionmentioning
confidence: 99%
“…(Pratheeshkumar and Kuttan, 2011b). Aberrant, sustained activation of NF-κB has been reported in numerous tumors and was implicated in various stages of photocarcinogenesis (Khan et al , 2012; Wang et al , 2012).…”
Section: Discussionmentioning
confidence: 99%